2015
DOI: 10.1007/s00167-015-3855-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic measurement of the posterior femoral offset is not precise

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…First, the use of plain radiographs preoperatively fails to account for chondral thickness, which may underestimate both PCO and AP femoral dimension. [17][18][19] If the average posterior condyle chondral thickness is approximately 1.7 mm medially and 2.0 mm laterally, 20 this would mean that our group with a reduction in PCO would actually have had an even greater decrease in PCO, pushing the average reduction to approximately 5.5 mm yet without any notable effect on ROM or outcomes, leaving this conclusion accurate. In contrast, the group with increased PCO may not have had as large of an increase in PCO when factoring in chondral thickness.…”
Section: Discussionmentioning
confidence: 87%
“…First, the use of plain radiographs preoperatively fails to account for chondral thickness, which may underestimate both PCO and AP femoral dimension. [17][18][19] If the average posterior condyle chondral thickness is approximately 1.7 mm medially and 2.0 mm laterally, 20 this would mean that our group with a reduction in PCO would actually have had an even greater decrease in PCO, pushing the average reduction to approximately 5.5 mm yet without any notable effect on ROM or outcomes, leaving this conclusion accurate. In contrast, the group with increased PCO may not have had as large of an increase in PCO when factoring in chondral thickness.…”
Section: Discussionmentioning
confidence: 87%
“…ment was found to be greater in males than females in two of three anatomic studies. Hence, customized arthroplasties designed with attention to the offset were probably important to subsequent restoration of function in patients requiring surgery, and care was often taken to consider this factor in treatment planning [39].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that conventional radiologic measurement is unreliable for both pre-and postoperative assessment. 15 van Lieshout et al 10 compared surgical techniques (flexion first balancer vs.…”
Section: León-muñoz Et Almentioning
confidence: 99%
“…The documentation of changes on plain conventional radiographs is questionable. 10,14,15 Only a few published studies comparing pre-and postoperative PCO consider cartilage thickness. 4,10,16 As shown in Figure 2, there is a discrepancy between the pre-(bones contours) and postoperative (prosthetic shapes) measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation